Integration Of Teachers And Parents In Inculcating Religious Values To Early Childhood At Tk Muslimat Pemalang - Akhsanul Fuadi; Siti Amanatun N.B (At-Tarbiyat, 2021)
The inculcation of religious values in early childhood is a vehicle for human formation to be a plenary figure who has good moral virtues and is devoted to Allah SWT. This research is a descriptive qualitative research, data collection using interview and documentation observation methods. The results of this study indicate that the inculcation of religious values in TK Muslimat Bulakan Belik Pemalang uses 6 methods, they are the habituation method, exemplary method, playing method, drill method, singing method, and the reward and punishment method. Of the six methods used each has advantages and disadvantages, but considered to have been quite successful and effective